Dust Explosion Characteristics of Agglomerated 35 nm and 100 nm Aluminum Particles - Hong-Chun Wu; Hsin-Jung Ou; Deng-Jr Peng; Hsiao-Chi Hsiao; Chung-Yun Gau; Tung-Sheng Shih (International Journal of Chemical Engineering)
In the experiment, nanoparticles of 35 nm Al and 100 nm Al powders, respectively, formed particles with average sizes of 161 nm and 167 nm in agglomeration. The characteristics of dust cloud explosions with the two powder sizes, 35 nm and 100 nm, revealed considerable differences, as shown here: (dp/dt)max-35 nm = 1254 bar/s, (dp/dt)max-100 nm = 1105 bar/s; Pmax-35 nm = 7.5 bar, Pmax-100 nm = 12.3 bar, and MEC-35 nm = 40 g/m3, MEC-100 nm = 50 g/m3. The reason of Pmax-35 nm value is smaller than Pmax-100 nm may be due to agglomeration. From an analysis of the explosive residue, the study found that nanoparticles of 35 nm Al powder became filamentous strands after an explosion, where most of 100 nm Al nanoparticles maintained a spherical structure, This may be because the initial melting temperature of 35 nm Al is 435.71°C, while that for 100 nm Al is 523.58°C, higher by 87.87°C. This study discovered that explosive property between the 35 nm Al and 100 nm Al powders after agglomeration were different.